Islam and Bugis Culture in Building The Character of The Luwu Society - Yunus, Yunus (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
The research was conducted using a qualitative approach to understand the social relations of the Tana Luwu community, who were the research targets. The researcher tries to reveal the multi-ethnic social relations of the Tana Luwu community using a qualitative approach and will present existing empirical findings. Values Adeq, saraq, sompeq is part of the survival of the Bugis people. In addition, he converted to Islam in the 1503 century in Tana Luwu, which greatly influenced people's lives in Tana Luwu. The values of Siri'na Pacce (Shame and Sepenanggungan) are highly popularized by the people in South Sulawesi and are considered to prevent someone from committing untimely actions. It turns out that Siri'na Pacce has proven that a value gives birth to pluralist character values (Sipakatau, Sipakalebbi, Sipakaingge), the values applied by the Luwu community so that there is no more ethnic and religious conflict occurring in Tana Luwu.